ANALISIS WEBSITE PERPUSTAKAAN UNIVERSITAS ISLAM NEGERI MENGGUNAKAN METODE BENCHMARKING DAN GOAL ORIENTED REQUIRMENTS ENGINEERING (GORE) MODEL (STUDI KASUS: UIN JAKARTA, UIN YOGYAKARTA DAN UIN MALANG) - Qurrotul Aini; Imam Marzuki Shofi; Fenty Eka Muzayyana Agustin (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2019)
The library is an important source of knowledge for all academicians. One of them is the university library, the purpose of the university library is funding support from the university in providing education by providing sources of scientific information in the library. However, information sources (consisting of web sites) available in the library are currently incomplete. For this reason, a usability evaluation and design analysis of the website is required so that the library website development goals can be achieved. Requirement Analysis of this library website used the Bechmarking and Goal Oriented Requirement Engineering (GORE) methods of three library websites namely the UIN Syarif Hidayatullah Jakarta library website, Sunan Kalijaga Yogyakarta UIN and UIN Maulana Malik Ibrahim. Benchmarking method is used to get the basic requirements by questionnaire. The GORE method is obtained based on the formulation of system objectives. To get the system requirements with the GORE method consists of actor models, Strategic Dependency diagrams, and Strategic Rationale diagrams. The results of this website analysis are the achievement of all requirements obtained and the new system of the library website of the Syarif Hidayatullah State Islamic University Jakarta